2011
DOI: 10.1590/s1517-83822010005000005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils against Vancomycin-Resistant enterococci (VRE) and Escherichia coli O157:H7 in feta soft cheese and minced beef meat

Abstract: Eleven essential oils (EOs) were evaluated for their antibacterial properties, against Vancomycin-Resistant Enterococci (VRE) and E. coli O157:H7. EOs were introduced into Brain Heart Infusion agar (BHI) (15ml) at a concentration of 0.25 to 2% (vol/vol) to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for each pathogen evaluated. Results showed that the most active essential oils against bacteria tested were thyme oil, with MIC 90 and MBC 90 for the VRA strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 21 publications
5
50
0
2
Order By: Relevance
“…The obtained results were in accordance with previous work by Selim (), which has confirmed the antibacterial efficiency in situ of thyme EO against E. coli inoculated in minced beef meat at 3 log CFU/g. In this case, the study of Selim (), demonstrated that the thyme EO, particularly from the concentration of 0.5 and 1% (vol/wt) can reduce the population‐level of the foodborne pathogen ( E. coli O157: H7). Thus, a bactericidal effect was obtained only after 3 days of storage.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results were in accordance with previous work by Selim (), which has confirmed the antibacterial efficiency in situ of thyme EO against E. coli inoculated in minced beef meat at 3 log CFU/g. In this case, the study of Selim (), demonstrated that the thyme EO, particularly from the concentration of 0.5 and 1% (vol/wt) can reduce the population‐level of the foodborne pathogen ( E. coli O157: H7). Thus, a bactericidal effect was obtained only after 3 days of storage.…”
Section: Resultssupporting
confidence: 92%
“…In fact, the initial populations of the pathogen (8 log CFU/g) on the untreated samples (control) were significantly increased and reached to 9.83 log CFU/g, after 15 days of storage. The obtained results were in accordance with previous work by Selim (2011), which has confirmed the antibacterial efficiency in situ of thyme EO against E. coli inoculated in minced beef meat at 3 log CFU/g.…”
Section: Antibacterial Effect Of Essential Oils In Situsupporting
confidence: 92%
“…After 10 days, the population of E. coli O157:H7 in the control sample was 6.10 log CFU g −1 , whereas the microbial count in the chicken tenderloin samples wrapped with the SSG–TEO film was 3.59 log CFU g −1 . Selim () also reported that the populations of E. coli O157:H7 in cheese and beef meat during storage at 7 °C for 14 days were significantly decreased by the addition of TEO. These results suggest that the addition of TEO into the SSG film could be an effective antimicrobial packaging method for chicken tenderloin.…”
Section: Resultsmentioning
confidence: 97%
“…Ground beef and other bovine products have often been implicated as sources of Stec (27), along with other food products (2,53,54). occasional outbreaks of Stec have also been associated with public drinking water (55) and swimming in contaminated water (25,28,46).…”
Section: Resultsmentioning
confidence: 99%